A Meningeal Syndrome Revealing A Tetanus in A Togolese: Case Report and Review of the Literature - AGBA Léhleng; ANAYO K Nyinèvi; DJALOGUE Lihanimpo; GUINHOUYA K Mensah; AWIDINA-AMA Awissoba; APETSE Kossivi; KUMAKO V. Kodzo; KOMBATE Damelan; BELO Mofou; BALOGOU K Agnon (Journal of Neurological Research And Therapy, 2019)
Although it is a vaccine-preventable disease, tetanus is frequently found in sub-Saharan Africa. Because of its rarity, this disease poses two problems for doctors of the 21st century: to make early diagnosis in order to refer patients to appropriate care structures, and to continue to ensure correct prevention of an affection that few current doctors have met. In it generalized form, the diagnosis of tetanus is easy, but when the beginning is localized, tetanus can be change with other diseases leading to a diagnostic wandering and a delay of adequate management. We report a case of tetanus in an 18-year-old male, who was received for neck pain and stiffness of the neck with a positive Kernig sign associated to fever since 48 hours. Initially treated for meningitis, the patient will develop at day 3 of hospitalization, the signs of generalized tetanus which led to evoked the diagnosis of tetanus. This diagnosis was reinforced by the notion of a rusty nail injury to the soles of the right foot 3 weeks before hospitalization and the absence of anti-tetanus vaccination. After using tetanus serum and vaccination with antibiotics (Metronidazole and Penicillin) and Diazepam in association with stripping of the wound under the foot, the patient was improved. This case illustrates that any neurological sign with the first trismus must evoke until proof of the contrary, a tetanus especially in case of association with a wound even if the immunization schedule is up to date.
Keywords: Meningeal syndrome